The Effect of Financial Results on Stock Prices Via Earnings Per Share: (A Case Study of the Food and Beverage Industry Listed on the IDX from 2017 to 2022) - Aristia Kamal; Fanlia Prima Jaya; Syamsuddinnor Syamsuddinnor (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Using a case study of the Food and Beverage industry listed on the Indonesia Stock Exchange (IDX) between 2017 and 2022, this study seeks to examine the partial impact of financial performance on stock prices through Earnings Per Share (EPS). Ratios like Return on Assets (ROA), Return on Equity (ROE), EPS, and share prices are used to gauge financial performance. Using a saturated sampling method, 18 firms were chosen for the sample. Using a quantitative technique with a descriptive approach, this study performs data analysis using Structural Equation Modeling (SEM) with the aid of SmartPLS version 3. 0. According to the study's findings, ROA has a considerable impact on EPS but not on share values. ROE has no discernible impact on stock prices or EPS. Nevertheless, EPS is shown to be a mediating variable between ROA and ROE, both of which have a substantial impact on share values. Improving the efficiency and effectiveness of financial management is one of the recommendations, particularly in areas that have an impact on EPS, such as capital structure and profitability. When making investment decisions, investors should pay attention to financial performance metrics like stock values, EPS, ROA, and ROE. To gain a more thorough analysis, future academics are urged to consider more variables, such the Price to Earnings Ratio, Dividend Payout Ratio, and external elements such as inflation and interest rates.